Pengaruh Pelatihan Good Parent untuk Menurunkan Agresi Verbal Orang Tua - ., Silviane (Persona:Jurnal Psikologi Indonesia, 2016)
This study with purpose, investigates the effects of good parent skills training to decreaseverbal aggression by parent. The experimental design-using pre-test, post-test with control group isapplied. Subject this sudy is 80 parets from GFC School Juanda, Sidoarjo East Java. 80 parentsgived pre test examined with verbal aggression questionnaire, 40 parent who received high score intest verbal aggression were randomly replaced in experimental and control groups. Each 20 parentsin experimental and 20 parents in control groups. During good parent training in experimentalgroup received about verbal agression and impact, comunication skills, and management stress in 3sessions of 5 hour in three weeks Then both experimental and controlgroups are measured withverbal aggression questionnaire post-tests. The results shows the deferences betwen mean pre testexperimental group and mean post test experimental group is 41,3500 P = 0,000 (< 0,05) that goodparent training has leaded to decreasing verbal aggression by parents.Keywords : Verbal Agression, Good Parent Training